Legal analysis of the fairness of bpjs health services based on law number 17 of 2023 concerning health - Arif Budiman (LEGAL BRIEF, 2025)
Fair access to health services is a fundamental right guaranteed by Indonesian law. BPJS Health, as the national health insurance administrator, is mandated under Law Number 17 of 2023 concerning Health to ensure equitable, non-discriminatory, and efficient services for all citizens. However, disparities in service quality, administrative delays, and unequal distribution of health facilities continue to raise legal concerns regarding the fulfillment of justice principles. This study employs a normative juridical approach supported by statutory, conceptual, and case-based analysis. Legal materials were collected through document review of Law No. 17/2023, related regulations, and scholarly literature. The analysis compares normative provisions with field-based findings from secondary data to evaluate whether BPJS services align with the principles of fairness, accountability, and legal certainty. Results: The study finds that although Law No. 17/2023 strengthens the legal foundation for equitable health services, gaps remain in implementation. Issues such as service discrimination, referral system barriers, and limited infrastructure hinder the realization of legal fairness. BPJS Health has implemented reforms to improve transparency and accessibility, yet inconsistencies between policy and practice persist. BPJS health services have a strong legal framework for fairness under Law No. 17/2023, but practical challenges weaken its effectiveness. Strengthening regulatory enforcement, improving governance, and enhancing health facility capacity are essential to achieving genuinely fair health services nationwide